Analysis on the Implementation of the Smoke-Free Area (SFA) Policy in Tanjungpinang - Gunnara, Harvensica; Daswito, Rinaldi; Mukodri, Dewi Mey Lestanti (Journal of Health Sciences and Epidemiology, 2025)
Indonesia has serious smoking problems, and all elements of society must engage in the process of smoking cessation. The smoking rate in the Riau Islands was relatively high among those aged > 15 years, and consumption patterns in Tanjungpinang show a 9.15% monthly per capita expenditure on tobacco products. This study aimed to analyze policy implementation regarding Smoke-Free Areas in Tanjungpinang using eight WHO indicators: Acceptability, Adoption, Appropriateness, Feasibility, Fidelity, Implementation Cost, Coverage, and Sustainability. This study was a policy implementation analysis. Key informants were four individuals from relevant agencies related to Smoke-free Area regulation, selected through purposive sampling. Qualitative data from eight WHO indicators were analyzed through content analysis. Implementing the smoking-free area (SFA) policy in the field was not yet optimal, especially in terms of supervision and the imposition of sanctions. Therefore, efforts to increase socialization and supervision are required to implement SFA policies more effectively.